2001
DOI: 10.1128/jb.183.8.2667-2671.2001
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Transmembrane-Segment (TMS) Version (ΔTMS VII-VIII) of the 14-TMS Tet(L) Antibiotic Resistance Protein Retains Monovalent Cation Transport Modes but Lacks Tetracycline Efflux Capacity

Abstract: A “Tet(L)-12” version of Tet(L), a tetracycline efflux protein with 14 transmembrane segments (TMS), was constructed by deletion of two central TMS. Tet(L)-12 catalyzed Na+/H+antiport and antiport with K+ as a coupling ion as well as or better than wild-type Tet(L) but exhibited no tetracycline-Me2+/H+ antiport inEscherichia coli vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 28 publications
3
39
0
Order By: Relevance
“…The P156A and C mutants may retain some electrogenic monovalent cation/proton antiport activity although they were negative for Tc-Co 2+ efflux. Several earlier mutants led to the hypothesis that although the efflux substrates share a binding site and translocation pathway, the most complicated substrate, the Tc-Co 2+ complex, required more elements to position it properly than the simpler monovalent cation efflux substrates (40,41,49). Together, the current observations suggest that Pro 156 is not essential for antiport but is very important in tight packing and "leak-proofing" in this critical region in both Tet(L) and Tet(K).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The P156A and C mutants may retain some electrogenic monovalent cation/proton antiport activity although they were negative for Tc-Co 2+ efflux. Several earlier mutants led to the hypothesis that although the efflux substrates share a binding site and translocation pathway, the most complicated substrate, the Tc-Co 2+ complex, required more elements to position it properly than the simpler monovalent cation efflux substrates (40,41,49). Together, the current observations suggest that Pro 156 is not essential for antiport but is very important in tight packing and "leak-proofing" in this critical region in both Tet(L) and Tet(K).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that these mutant Tet(L) proteins promote leakage of K + into the vesicles in response to the generation of the transmembrane potential, ΔΨ, while such a leak is not observed in wild type Tet(L) vesicles or with other Tet(L) mutants (e.g. see Figure 3) (40,41,49). The activity in the complete assay, with both electron donor and intravesicular K + , was lower than wild type in each Pro 156 mutant ( Figure 4).…”
Section: Mutants Of Pro 156 In the Motif C Gp Dipeptidementioning
confidence: 99%
See 2 more Smart Citations
“…For assays of Tc r , 10 l of stationary-phase cultures of the E. coli DH5␣ transformants with various tet genes expressed from pBK15 was inoculated into 2 ml of LBK medium containing a TC concentration of 0, 2, 4, 8, 10, 12, 16, or 32 g/ml. The data for growth (A 600 ) at 15 h were plotted for determinations of the MIC (26). For assays of complementation of the K ϩ uptake defect of E. coli TK2420, 10 l of a stationary-phase culture was inoculated into defined medium (9) containing KCl concentrations from 5 to 25 mM.…”
Section: Methodsmentioning
confidence: 99%